2021
DOI: 10.1037/dev0001236
|View full text |Cite
|
Sign up to set email alerts
|

Parent–adolescent relationship quality as a moderator of links between COVID-19 disruption and reported changes in mothers’ and young adults’ adjustment in five countries.

Abstract: The COVID-19 pandemic has presented families around the world with extraordinary challenges related to physical and mental health, economic security, social support, and education. The current study capitalizes on a longitudinal, cross-national study of parenting, adolescent development, and young adult competence to document the association between personal disruption during the pandemic and reported changes in internalizing and externalizing behavior in young adults and their mothers since the pandemic began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 63 publications
2
46
0
1
Order By: Relevance
“…At age 20, young adults completed Experiences with COVID-19, a measure designed to provide a quick assessment of perceived changes in psychosocial functioning, interpersonal relationships, attitudes, and behaviours related to pandemic restrictions, and other personal experiences with the pandemic; the development of this measure based on other community-wide disasters and stressors is described elsewhere (Skinner et al 2021). Depending on the site, young adults completed this measure between late March of 2020 and early January of 2021.…”
Section: Experiences During Covid-19mentioning
confidence: 99%
“…At age 20, young adults completed Experiences with COVID-19, a measure designed to provide a quick assessment of perceived changes in psychosocial functioning, interpersonal relationships, attitudes, and behaviours related to pandemic restrictions, and other personal experiences with the pandemic; the development of this measure based on other community-wide disasters and stressors is described elsewhere (Skinner et al 2021). Depending on the site, young adults completed this measure between late March of 2020 and early January of 2021.…”
Section: Experiences During Covid-19mentioning
confidence: 99%
“…The contributions to this special issue indicate that the pandemic and the measures affected aimed to prevent the virus from spreading impacted families across different levels of the family system, such as: (a) changed family routines and rules (Bülow et al, 2021; Eales et al, 2021) and increased chaos (Cassinat et al, 2021) at the family level; (b) both positive (Donker et al, 2021) and negative (McRae et al, 2021) changes in the qualities of the caregiver-child relationship at the dyadic level; and (c) changes in the wellbeing of individual family members, as evidenced by increased worry, concern, sadness, and stress in caregivers (Eales et al, 2021) and higher levels of internalizing (Gadassi Polack et al, 2021) and externalizing problems (Skinner et al, 2021) in children and adolescents.…”
Section: The Impact Of the Covid-19 Pandemic On Families And Childrenmentioning
confidence: 99%
“…Families already experiencing more negative interactions before the pandemic tended to have more difficulties adjusting during the pandemic, possibly further accentuating difficulties between family members (Qu et al, 2021; Sun et al, 2021). At the same time, positive family functioning seemed to buffer against the effects of the pandemic (McRae et al, 2021; Skinner et al, 2021). These findings suggest that the pandemic disproportionally affects children, caregivers and families who are already at risk, either through limited resources at the relationship level, or through other well-known risk factors, such as low socioeconomic status and mental health vulnerabilities.…”
Section: Differential Impact Of the Covid-19 Pandemic On Families And...mentioning
confidence: 99%
“…Other studies in the special issue indicated how pandemic disruptions can undermine family relationships, functions such as parenting, and cohesion at the family level (e.g., Cassinat et al, 2021; Donker et al, 2021; McRae et al, 2021; Peltz et al, 2021). Multiple studies also observed how pandemic changes affected the individual well-being of parents and youth, along with increasing fears, stress, and uncertainty (Gadassi Polack et al, 2021; Peltz et al, 2021; Skinner et al, 2021). In the study by Cassinet and colleagues (2021), consistent with family stress theory, chaos in the family increased during the spring of 2020 during a pandemic shutdown period.…”
Section: Conceptual Themes In the Special Issue: Multisystem Perspect...mentioning
confidence: 99%
“…Based on the first two waves of a longitudinal study, Browne and colleagues (2021), for example, utilized a new measure of pandemic-related family stressors developed and validated by their team (Prime et al, 2021) to test their Family Disruption Model (Prime et al, 2020), predicting and finding that caregiver-reported COVID disruption was related to family distress and dysfunction and mental health problems in their children. In their study of five countries drawn from an ongoing international study, Skinner and colleagues (2021) linked personal perceptions of COVID disruption reported by mothers and their young adult children (age 20) to their reports of increased internalizing and externalizing problems during the pandemic.…”
Section: What Matters For Families Responding To the Pandemic?mentioning
confidence: 99%